Sustainable Marketing Strategy for Wana Karsa Ubud Hotel as a Local Brand at Post Pandemic - Andhy Putra, I Putu Bagus (Riviera Publishing, 2023)
Wana Karsa Ubud Hotel is a hotel located on Jalan Monkey Forest Ubud and is owned by local people using a local brand. After reopening post-pandemic in early 2022, Wana Karsa Ubud Hotel is recovering gradually and is required to have a sustainable marketing strategy that is appropriate in facing competition from many competing hotels around it. The purpose of this research is to analyze the factors that can hinder and encourage the implementation of sustainable marketing at Wana Karsa Ubud Hotel and analyze sustainable marketing strategies that can be implemented. This research method uses a qualitative approach with a sample of 22 respondents consisting of 8 hotel employees, 4 clients who work for agents who work with the Wana Karsa Ubud Hotel, and 10 guests who stay at the Wana Karsa Ubud Hotel. Data collection was carried out through the distribution of questionnaires, interviews, observations, and literature studies. Data analysis techniques use the IE matrix (internal - external) and SWOT matrix analysis. The results of sustainable marketing strategy research at Wana Karsa Ubud Hotel as a post-pandemic local brand also found sustainable marketing strategies that can be implemented at Wana Karsa Ubud Hotel with reference to sustainable marketing theories such as: customer oriented, customer value, innovative marketing, sense of mission marketing, and social marketing. This research has implications that help identify specific barriers and hurdles that need to be overcome for successful implementation as well.